Práticas pedagógicas no curso de pedagogia : para uma relação entre teoria e prática - Machado, Viviane Guidotti (2017)
This thesis was developed in the line of research Formation, Government and Practices in Education, in the Stricto Sensu Doctorate Course, the Graduate Program in Education, the School of Humanity, of the Pontifical Catholic University of Rio Grande do Sul. The central problem of this research has proposed a study centered on pedagogical practices developed in teaching and classroom learning processes, having as principal interrogator-teachers of the Degree Course of Pedagogy, a Federal Public Institution of the Northeast of the countryside. Do these formers develop their pedagogical practices in order to favor the production of knowledge from the problem between theory and practice in the classroom. In this way, the objective of this research was to understand the organization of pedagogical practices in a Degree Course of Pedagogy in the direction of the articulation between theory and practice in the classroom. The theoretical justification was based on the following topics: The trajectory of the course of pedagogy in Brazil, the pedagogical trends in Brazil and the pedagogical practices. The qualitative approach of research was developed by using the principles of a case study (LÜDKE; ANDRÉ, 1986). The data was collected by three instruments: a very structured interview, documents elaborated and published by the Institution chosen for this study, and the roaming journals (BARBIER, 2007) that recorded experiences in the empirical field during data collection. To analyze and interpret the data of the interviews and the documents of IES was used the qualitative analysis of Textual Analysis Discursive of Moraes and Galiazzi (2011). The main findings point to understanding the organization of pedagogical practices that is set up urgently in the construction of an interdisciplinary curriculum for teacher´s formation, which provides a relationship between theory and practice, aiming to form a teacher consisting of characteristics such as: reflective, critical and researcher, from the recognition and appreciation of their socio-cultural realities and the academics of the Degree Course of Pedagogy. The data points to rethink the distance from the University and the grade school, as well as reviewing the demands and labor conditions of teacher’s trainers. And we also need to rethink the Degree Course of Pedagogy beyond the construction of a teacher in the classroom, it must be recognized that this professional is also crucial in other working environments involving teaching and learning.